PENYELESAIAN SENGKETA TANAH ADAT MELALUI PROSES PERADILAN - Ana Suheri (MORALITY: Jurnal Ilmu Hukum, 2019)
Customary rights in the colonial era were often ignored. Due to the mention of customary rights in the Basic Agrarian Law, which essentially also means recognition of those rights, basically the customary rights will be considered as long as the rights are in fact still in the legal community concerned. For example, in granting a right to land (for example, the right to use a business), the indigenous peoples concerned will be heard beforehand and will be given directions that they have the right to receive as the customary rights holders.